Severe Posterior Reversible Encephalopathy in Pheochromocytoma: Importance of Susceptibility-Weighted MRI - Serter, Asli (The Korean Society of Radiology, 2013)
Pheochromocytoma is a rare cause of hypertension in children. Hypertension is one of the common reasons of posterior reversible encephalopathy. Intracerebral hemorrhage is a serious and unexpected complication of hypertensive encephalopathy due to pheochromocytoma, and very rarely seen in the childhood. Intracerebral hemorrhages should be searched if there are hypertensive reversible signal changes on the brain. Susceptibility weighted imaging (SWI) is a more sensitive method than conventional MRI when demonstrating cerebral microhemorrhagic foci. This is the first report of SWI findings on intracerebral hemorrhages in basal ganglia, brain stem and periventricular white matter due to hypertensive encephalopathy in a child with pheochromocytoma.